PEMBELAJARAN MENULIS PUISI DENGAN MENGUNAKAN METODE PROJECT BASED LEARNING BERBATUAN MEDIA AUDIO VISUAL - wiwin, wiwin; Wikanengsih, Wikanengsih; Suhara, Alfa Mitri (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
The activity of putting ideas into writing makes students feel difficult, especially in choosing diction, figure of speech, pengimajian and concrete words in making a poem. Therefore, it is necessary to have interesting learning media and methods in order to assist students in putting ideas and ideas into their writing. This is related to the research objectives, namely to examine the implementation of learning to write poetry, examine the responses of teachers and students and examine the difficulties experienced by students in learning to write poetry by using a project based learning model assisted by audio visual media in class x even semester students at MAN. 1 Bandung City for the 2019-2020 academic year which was held in February 2020 for 3 meetings. The subjects in this study were 33 students. This research method is carried out by using a qualitative descriptive method. The data instrument was obtained using observation sheets, questionnaires, and tests. The data analysis technique used is in the form of scores from the results of the tests carried out as the final results. The criteria for the success of this research can be seen from the increase in the success of the processes and products produced. The results of the observation sheet when accumulated from three meetings for teacher activities get a score of 89% with the high category and three meetings. The results of the student questionnaire during the three meetings got a score of 80.3% in the high category. The activity of putting ideas into writing makes students feel difficult, especially when writing text in choosing diction, figure of speech, pengimajian and concrete words in making a poem. Even so, students can finish it well, and some students get scores above the KKM. From the data above, it can be concluded that learning to write poetry using the project-based learning method assisted by audio-visual media is very effective in learning to write poetry.